Hubungan keberadaan TPA Sampah Sowi Gunung terhadap pengembangan kawasan permukiman di Distrik Manokwari Selatan - Deslan Dayan Siagian; Eko Agus Martanto; Meike M Lisangan (Program Pascasarjana Universitas Papua, 2023)
The main focus of this research is to examine the impact of the existence of the Final Processing Site (TPA) on the physical condition of the surrounding environment and the socio-economic conditions of the surrounding community. In this study, physical conditions were measured based on Surface Water Conditions, Shallow Ground Water Conditions/Wells, Air Quality, and Soil Quality. The impact on the socio-economic conditions to the community was measured based on the emergence of new livelihoods, health, and main livelihood income. The data will be analyzed using the Spearman Rank correlation method, where the X variable is the impact of the presence of the landfill and Y1-Y7 variables were the impact on the physical environment and socio-economic conditions of the community. The results of this study are that the physical condition of the waste landfill in Sowi Gunung has a negative impact on the community and the environment around the landfill. The social conditions caused by the landfill in Sowi Gunung do not affect the people living around the landfill. The correlation analysis of the relationship between the existence of the Sowi Gunung Final Disposal Site (TPA) on physical environmental conditions including surface water, shallow groundwater/wells, air quality, soil quality with low to very low correlations. The correlation between the socio-economic conditions of the community: livelihoods, health, and income around the TPA, has a low to very low correlation.